2018
DOI: 10.1096/fj.201800373r
|View full text |Cite
|
Sign up to set email alerts
|

FoxA2 regulates the type II collagen–induced nucleus pulposus–like differentiation of adipose‐derived stem cells by activation of the Shh signaling pathway

Abstract: Adipose tissue-derived stem cell (ADSC)-based therapy is promising for the treatment of intervertebral disc (IVD) degeneration, but the difficulty in inducing nucleus pulposus (NP)-like differentiation limits its clinical applications. Forkhead box (Fox)-A2 is an essential transcription factor for the formation of a normal NP. We demonstrated that type II collagen stimulates NP-like differentiation of ADSCs, partly by increasing the expression of FoxA2. We constructed FoxA2-overexpressing and -knockdown ADSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Human ADSCs are multipotent cells characterized by their ability to differentiate into adipocytes, chondrocytes, and osteoblasts [ 42 ]. Previous studies have demonstrated the beneficial effect of mesenchymal stem cells on intervertebral disc degeneration [ [43] , [44] , [45] ]. But there are still many problems between the microenvironment and transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Human ADSCs are multipotent cells characterized by their ability to differentiate into adipocytes, chondrocytes, and osteoblasts [ 42 ]. Previous studies have demonstrated the beneficial effect of mesenchymal stem cells on intervertebral disc degeneration [ [43] , [44] , [45] ]. But there are still many problems between the microenvironment and transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Shh protein expression level has also been shown an increase when crosslinked scaffolds promoted ADSC proliferation and differentiation into NP-like cells, indicating that the activation of the Shh signaling pathway might play a regulatory role in directional differentiation (Zhou et al, 2018b). In addition, NP-like cell differentiation induced by Collagen type II is related to FoxA2 overexpression and can be rescued by a Shh signaling pathway inhibitor (Zhou et al, 2018a).…”
Section: Signaling Pathways Involved In Biomaterial-induced Ivd-like mentioning
confidence: 98%
“…When ADSCs were embedded in Collagen type II hydrogels compared with Collagen type I hydrogels, an upregulation of Collagen type IIA, collagen type IIB and aggrecan gene expressions and stronger alcian blue staining were observed, indicating a more pronounced differentiation of ADSCs to the cartilage lineage (Lu et al, 2008). Collagen type II alone has been shown to induce ADSC differentiation into NP-like cells (Zhou et al, 2018b), which was related to FoxA2 overexpression (Zhou et al, 2018a). Moreover, Collagen type II combined with other natural components and crosslinkers, such as chondroitin sulfate (Zhou et al, 2018c), hyaluronan (Calderon et al, 2010), genipin (Zhou et al, 2018b), N,N-(3-dimethylaminopropyl)-N -ethylcarbodiimide and N-hydroxysuccinimide (EDAC/NHS) , to modify its porosity and other micromechanical properties has also been shown to exert an improved effect on stem cell proliferation and directional differentiation.…”
Section: Biochemical Componentsmentioning
confidence: 99%
See 2 more Smart Citations